Dampak Sosial Ekonomi Masyarakat Penerima Bantuan Langsung Tunai Masa Pandemi COVID-19 di Kota Tanjungpinang - Emmy Solina; Aspariyana Aspariyana; Mahadiansar Mahadiansar (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to examine the conditions of the people of Tanjungpinang City who receive Direct Cash Assistance (BLT) which will affect the socio-economic impact during the COVID-19 pandemic. The research method uses descriptive qualitative by using various relevant sources for in-depth analysis of secondary data by looking at the current phenomenon in a crisis condition. The results show that the socio-economic impact of the people of Tanjungpinang City in receiving BLT and not receiving BLT is the presence of new social interactions and efforts to adapt to new environments so that the perspective of adopting new habits can be applied by maintaining health protocols to prevent the spread of the COVID-19 pandemic. In addition, the researchers also gave suggestions to the central government to communicate intensively to local governments so that they continue to supervise the provision of BLT so that it can be allocated to the right target community and be useful in the sustainable use of BLT in Tanjungpinang City.